1982
DOI: 10.1152/ajprenal.1982.243.4.f356
|View full text |Cite
|
Sign up to set email alerts
|

Redox state of cytochrome aa3 in isolated perfused rat kidney

Abstract: Optical spectroscopy was used to evaluate mitochondrial anoxia in the isolated perfused rat kidney by determining the percentage of cytochrome aa3 in the reduced state. Despite high levels of plasma flow (greater than 20 ml . g-1 . min-1) and venous PO2 (greater than 300 mmHg), 25--40% of cytochrome aa3 appeared to be in its reduced form. Agents that alter metabolism or transport primarily in renal cortex had little or no effect on the redox state of cytochrome aa3. These included 3-mercaptopicolinate, an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…By improving local oxygenation, furosemide reduces HIF-1 expression in the outer and inner medulla (Zou et al, 2001). In the isolated perfused rat kidney, furosemide and bumetanide (the other NKCC inhibitor) reduced the amount of cytochrome c oxidase existing in the reduced state from 40 to 20% (Epstein et al, 1982). Likewise, in the intact anesthetized rat, furosemide increased medullary pO 2 from 16 to 35 mm Hg (Brezis et al, 1994).…”
Section: Hypoxia In the Renal Medulla And Its Role In Local H 2 S Sigmentioning
confidence: 97%
See 1 more Smart Citation
“…By improving local oxygenation, furosemide reduces HIF-1 expression in the outer and inner medulla (Zou et al, 2001). In the isolated perfused rat kidney, furosemide and bumetanide (the other NKCC inhibitor) reduced the amount of cytochrome c oxidase existing in the reduced state from 40 to 20% (Epstein et al, 1982). Likewise, in the intact anesthetized rat, furosemide increased medullary pO 2 from 16 to 35 mm Hg (Brezis et al, 1994).…”
Section: Hypoxia In the Renal Medulla And Its Role In Local H 2 S Sigmentioning
confidence: 97%
“…In most cells in the body, cytochrome c oxidase is almost completely oxidized under physiological conditions because its K m for oxygen is attained at only 1 to 2 mm Hg in isolated mitochondria and at approximately 10 mm Hg in the whole cells, which is much less than ambient pO 2 in these tissues. However, in medullary tubular cells, 20 to 40% of cytochrome c oxidase exists in the reduced state, indicating that local pO 2 is close to critical at which mitochondrial respiration might be compromised (Epstein et al, 1982). Due to low pO 2 , the expression of a major molecular target of hypoxia, hypoxia-induced factor-1 (HIF-1), and its target genes, such as inducible NO synthase, cyclooxygenase-2 (COX-2), and heme oxygenase-1 (HO-1), is much higher in the medulla than in the cortex.…”
Section: Hypoxia In the Renal Medulla And Its Role In Local H 2 S Sigmentioning
confidence: 99%
“…The mTAL are nourished only through the descending VR that are capable of providing an amount of oxygen barely exceeding basal needs. With the outer medulla operating on the brink of hypoxia (18,50), either a reduction of blood supply or an increased metabolic load can generate greater amounts of ROS production in the mTAL. The metabolic work of the mTAL is increased as more Na ϩ is delivered to the loop of Henle, an event that occurs with a rise in renal perfusion pressure or a greater filtration of NaCl as seen with high-salt feeding, hypertension, and the early stages of diabetes (134,154,196,202).…”
Section: ·ϫmentioning
confidence: 99%
“…Recent observations by Epstein et al (3) using organ spectrophotometry in whole isolated perfused kidneys, have indicated that a significant fraction (20-40%) of cytochrome a,a3 (cytochrome c oxidase) as sensed by this technique is reduced but becomes more oxidized when mTAL transport is decreased by furosemide (3). Cytochrome a,a3 is normally 95-98% oxidized in the presence of oxygen at partial pressures that fulfill the needs of oxidative phosphorylation (4).…”
Section: Introductionmentioning
confidence: 99%